Analisis Penyelesaian Sengketa Ekonomi Syariah Secara Non Litigasi - Ana Latifatuz Zahro; Muhammad Iqbal Fasa; A. Kumedi Ja’far (Reslaj : Religion Education Social Laa Roiba Journal, 2022)
The aims and objectives of the research are to find out the practice of resolving sharia economic disputes in a non-litigation manner and the application of sharia economic dispute auctions. In order to achieve the aims and objectives, this research uses a normative juridical research method with an approach that refers to the Qur'an, Al-Hadith, ijtihad, legal theory, legal principles and legislation. Sources of data are obtained from the Qur'an, Al-Hadith, books, laws and regulations, court decisions, and so on as long as they are interrelated. The practice of resolving sharia economic disputes in a non-litigation manner can be pursued by arbitration, namely through the Sharia Arbitration Board (“Basyarnas-MUI”) and by alternative dispute resolution methods, namely through Consultation, Negotiation, Mediation or Expert Assessment. This is related to arbitration through the Basyarnas-MUI for the procedures and procedures that have been regulated. Meanwhile, alternative dispute resolution by means of Consultation, Negotiation, Mediation or Expert Assessment has not been sufficiently regulated. Despite this, there is already a National Committee for Islamic Economics and Finance (KNEKS) whose function is to formulate and provide recommendations for solving problems in the Islamic economy and finance sector. In addition to that, there are also arbitration institutions and other alternative dispute resolution, but these institutions have not specifically regulated the non-litigation settlement of sharia economic disputes. The application of sharia economic dispute auctions can be carried out on material guarantees by means of parate execution, executive titles or underhand sales. However, against the auction mechanism, the debtor can still take legal action, namely the cancellation of the auction or resistance / objection to the auction. This of course, apart from being less effective, it does not provide as intended the purpose of the law and legal protection for interested parties.